Anaplastic thyroid carcinoma presenting as bilateral pleural effusion - Sodhi, R. (Medknow Publications & Media Pvt Ltd, 2014)
Anaplastic thyroid cancer presenting as bilateral malignant pleural effusion is rarely reported. We present a case who presented solely with respiratory symptoms and subsequently found to be having bilateral malignant pleural effusion secondary to anaplastic thyroid cancer.